PENGARUH PAKAN DARI AMPAS TAHU YANG DIFERMENTASI DENGAN EM4 TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Rasyidah, Silfia - (STKIP PGRI Sumbar, 2014)
The available of woof in enough quantities, in time, and marked as good nutritious is one of factorswhich is very important in fish cultivation. Made woof factory which is usually used by fish breeder for fishcultivation which is getting expensive, because the increase of basic material price of woof, especially fish flouras main protein source which is used in made fish woof. The effort which can be done to press the basicalternative woof as substitute half of woof basic material by using tofu waste. Related on it that is done by theresearch purpose to know the influence woof from tofu which is differmentation with EM4 to nila fish growth(Oreochromis niloticus).This research is done in Zoology Laboratory Padang State University in March untilMay 2014. The design of tried which is used Rancangan Acak Lengkap (RAL) by using 4 actions and 6repeatation with A control (Palette PF800), B (tofu waste fermentation 14%), C (tofu waste fermentation 24%),and D (giving tofu waste 34%). This research is done for 8 weeks to see nila fish growth. The data analysis byvarious analysis and continued by differential test (continuous test).The result of research that woof is givenfrom tofu differmentation by EM4 to nila fish give influence is not real to long growth and woof conversion in Î±5%, give very real in weight addition in Î±1%, the itâs continued by continuous test DNMRT. From the researchresult can be concluded that giving the woof of tofu waste fermentation 24% can increase Nila fish growth. So infish cultivation can use made woof by themselves to solve woof price which is very expensive so that it canconclude production result.